Technological ecologies & sustainability - Heidi A. McKee (Utah State University Press/ Computers and Composition Digital Press, 2009)
Together, computerized writing environments (e.g., physical spaces, hardware, software, and networks) and the humans who use and support such technologies comprise complex ecologies of interaction. As with any ecology, a human-computer techno-ecological system needs to be planned, fostered, designed, sustained, and assessed to create a vibrant culture of support at the individual, programmatic, institutional, and even national and international level. Local and larger infrastructures of composing are critical to digital writing practices and processes. In academia, specifically, all writing is increasingly computer-mediated; all writing is digital. Unfortunately, at far too many institutions, it is difficult to sustain ecologies of digital writing. How then to best plan, foster, design, sustain, and assess the complex ecologies framing the study and practice of digital writing that we do (or hope to do) as teachers, scholars, learners, and writers? The audience for this collection is teachers, scholars, administrators, and graduate students working in fields of composition studies, computers and writing, technical/professional communication, literature, education, and English education. We all face the same dilemma: More and more of our work and instruction takes place in electronic environments, but budget constraints and assessment mandates loom, and often our positions within or institutions prohibit us from active participation in central computing endeavors. This necessarily multivocal collection refines our discussions of the many components of sustainability, providing contextual, situated, and flexible modes and methods for theorizing, building, assessing, and sustaining digital writing ecologies. Section I: Sustaining instructors, students, and classroom practices. Introduction to section I / Heidi McKee -- Political economy and sustaining the unstable : new faculty and research in English studies / Kelli Cargile Cook, Ryan (Rylish) M. Moeller, and Cheryl E. Ball -- A portable ecology : supporting new media writing and laptop-ready pedagogy / Kristie S. Fleckenstein, Fred Johnson, and Jackie Grutsch McKinney -- Stifling innovation : the impact of resource-poor techno-ecologies on student technology use / Anthony T. Atkins and Colleen A. Reilly -- Video for the rest of us? Toward sustainable processes for incorporating video into multimedia composition / Peter J. Fadde and Patricia Sullivan -- Portfolios, circulation, ecology, and the development of literacy / Kathleen Blake Yancey -- Section II: Sustaining writing programs. Introduction to section II / Danielle Nicole DeVoss -- The administrator as technorhetorician : sustainable technological ecologies in academic programs / Michael Day -- Sustainability and digital technology : program analysis via a "three-legged" framework / Patricia Ericsson -- The hybrid academy : building and sustaining a technological culture of use / Beth L. Brunk-Chavez and Shawn J. Miller -- Using the LEED evaluation tool to assess the sustainability of first-year computers and writing programs / Kip Strasma -- Digital studio as method : collaboratively migrating theses and dissertations into the technological ecology of English studies / Jude Edminster, Andrew Mara, and Kristine Blair -- Section III: Sustaining writing center, research centers, and community programs. Introduction to section III / Dickie Selfe -- Sustaining a research center : building the research and outreach profile for a writing program / James E. Porter -- Sustaining community and technological ecologies : what writing centers can teach us / Jeanne R. Smith and Jay D. Sloan -- Sustaining (and growing) a pedagogical writing environment : an activity theory analysis / Mike Palmquist, Kate Kiefer, and Jill Salahub -- Genre-informed implementation analysis : an approach for assessing the sustainability of new textual practices / Lisa Dush -- Section IV: Sustaining scholarship and the environment. Introduction to section IV / Danielle Nicole DeVoss -- Sustainable digital ecologies and considered limits / Lisa Lebduska -- Old world successes and new world challenges : reducing the computer waste stream in America / Shawn Apostel and Kristi Apostel -- Sustaining scholarly efforts : the challenge of digital media / Cynthia L. Selfe, Gail E. Hawisher, and Patrick W. Berry -- Afterword : sustainable writing programs : a continuing agenda / Charlie Moran -- Author biographies and photos.